FIRM HETEROGENEITY, MULTIPLANT CHOICE, AND AGGLOMERATION1. (21st September 2014) - Saito, Hisamitsu
ABSTRACT We examine the organization and location choice of heterogeneous firms in a two‐region economy. When some high‐productivity firms engage in multiplant production, a reduction in transport costs causes two changes in a small region: the closure of plants by high‐productivity multiplant firms and the relocation of low‐productivity single‐plant firms to the region. In the presence of high‐productivity multiplant firms, therefore, a decline in transport costs reinforces the spatial sorting of firms by productivity, enlarging the productivity gap between large and small regions. Conversely, reducing investment costs weakens the spatial sorting effects on regional productivity disparities.